An Overview of Preschool Children’s Reasons for Preferring Colorful and Sweet Beverages - Budi, Agung Putra Setiya; Yulianti, Natalia Ratna; Wahyuningrum, Eka (Sahabat Publikasi Kuu, 2025)
Introduction: Contemporary children tend to choose packaged beverages such as tea, soda, and energy drinks, which contain high levels of sugar. The International Diabetes Federation (IDF) reported in 2021 that there were 1.2 million cases of diabetes mellitus among children aged 0–19 years. In Central Java, the prevalence of obesity among children aged 5–12 years reached 6% in 2024. Previous studies have focused solely on children’s dietary consumption patterns; however, the reasons why children prefer colorful and sweet beverages have not been explored. Moreover, prior research often involved only parents, teachers, or health workers, which does not fully capture children’s own perspectives. Therefore, the aim of this study was to explore the reasons preschool children prefer consuming colorful and sweet beverages. Method: This study employed a quantitative design with a descriptive approach. The sample consisted of all preschool children enrolled at Bina Atmaja Kindergarten in Semarang, totaling 25 children. A total sampling technique was applied. Data were collected through questionnaires completed by the preschool respondents and analyzed using descriptive statistical analysis. Result: Respondents who purchased beverages because of their sweet taste totaled 21 children (83%). A total of 19 respondents (76%) were influenced by the low price, 14 respondents (56%) reported parental permission, and 12 respondents (48%) cited attractive colors as the reason for purchasing the drinks. Conclusion: Sweet taste was the most frequently reported reason preschool children consumed colorful and sweet beverages.